Readings in Indian Christian theology - Sugirtharajah, R. S. (Rasiah S.); Hargreaves, Cecil; I.S.P.C.K. (Organization) (Delhi : ISPCK, 1995)
Contributed articles.
Includes index.
"Suggestions for further reading": v. 1, p. 249-251.
Keywords: Theology, Doctrinal -- India -- History